Economic costs of large public sector deficits and high inflation: The Argentine lesson - Bernhard Fischer; Peter Trapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
The objective of this paper is to analyse the Argentine experience of large public sector deficits and high inflation, to elaborate the collection and dynamics of the inflation tax used to public financing and to identify the economic costs of this policy. Strong references are made to the experiences of other countries during periods of high inflation. Finally, some policy options are dealt with.
Keywords: 330